When Should Surgical Human Subject Research Involve Patients Who Are Incarcerated? - Khan, Lubna; Hoffman, Marcus (AMA Journal of Ethics, 2025)
Surgical research involving patients who are incarcerated is fraught with ethical, logistical, and practical questions. This article first considers important moments in the history of research with people who are incarcerated and suggests how they have contributed to evolution in human subject research ethics and regulation. This article also examines the problem of limited data about surgical disease burden and describes barriers to enrolling individuals who are incarcerated in surgical clinical trials, including study exclusion criteria and clinician-investigator bias. Finally, this article recommends strategies for balancing human research subject protections with the need for equitable enrollment in surgical clinical trials, especially later-phase trials in which benefit is more likely than in early-phase trials.